Healthy Wetlands, Healthy People: Educating and Mobilizing Youths for Reducing Water Pollution and Sedimentation in Lakes of Pokhara Valley, Nepal - Kafle, Mohan (Journal of Wetlands Ecology, 2008)
No abstract. Journal of Wetlands Ecology Vol.1(1/2) 2008, p.14